Spatial accessibility and functional layout impacts on urban underground space development: a case study of Shanghai. Issue 1 (March 2021) - Dong, Yun-Hao; Peng, Fang-Le; Xing, Xiao; Wu, Xiao-Lei
Abstract: Over the past decade, China's megacities such as Shanghai and Beijing have witnessed great progress in their metro networks. With the rapid development of metro system, urban underground space (UUS) in China has been widely utilized in a systematic manner, following the principles of transit-oriented development. A comprehensive understanding of the impacts of the built environment on UUS is doubtlessly conducive to the high-quality and sustainable urban development. However, there are fewer researches conducted to study the impacts on UUS compared with those studies focusing on ground level space. Moreover, quantitative researches using multi-source big data on underground space are limited, which makes it hard to reveal the development regulation with high-precision at a large scale. This paper aims to study the impacts of spatial accessibility and functional layout on UUS. Shanghai, as one of the most prosperous megacities in China with well-developed underground space, was selected as the case study. In this paper, open data from Open Street Map and Point of Interest (POI) in AMAP was adopted. Indices such as integration (index of space syntax) of metro line, road length, road density, POI density, and entropy of POI were chosen to reflect the spatial accessibility and functional layout. Underground POI (UPOI) density was set as a proxy of UUS development intensity. A quantitative analysis using multiple linear regression model was conducted. The results showed that both two kinds of indices strongly correlated to the underground space development, whereas the influences of selected indices on UUS were different. At last, the characteristics of UUS in Shanghai and further development strategies were discussed, which provided a perspective of smart growth for planners, designers and authorities.